2007
DOI: 10.1002/srin.200706268
|View full text |Cite
|
Sign up to set email alerts
|

Equlibrium between Liquid Fe‐Ti‐O Slags and Metallic Iron

Abstract: The compositions of Fe‐Ti‐O melts in equilibrium with molten iron have been determined by melting mixtures of TiO2, metallic iron and various additions of either Fe2O3 or metallic titanium in a high‐frequency induction furnace. The furnace had a vertically segmented water‐cooled copper crucible which enabled the mixture to be melted with vigorous stirring inside a freeze‐lining of about 1 mm thickness. The slag compositions were found to form a curved line in the ternary diagram FeTiO3 – TiO2 – Ti2O3 with its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 4 publications
3
12
0
Order By: Relevance
“…In earlier work reported by Eriksen et al 1, Elstad et al 2 and Seim and Kolbeinsen 3 synthetic high titania slags were produced using a high frequency induction furnace with a water cooled copper crucible. Eriksen et al 1 proposed an equilibrium line between the molten slag and metallic iron based on own experimental data and previously published data 4, 5. The proposed line is also in good agreement with the line earlier published by Rosenqvist 6.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier work reported by Eriksen et al 1, Elstad et al 2 and Seim and Kolbeinsen 3 synthetic high titania slags were produced using a high frequency induction furnace with a water cooled copper crucible. Eriksen et al 1 proposed an equilibrium line between the molten slag and metallic iron based on own experimental data and previously published data 4, 5. The proposed line is also in good agreement with the line earlier published by Rosenqvist 6.…”
Section: Introductionmentioning
confidence: 99%
“…This work resulted in a new suggested equilibrium line between the liquid high titania slag and liquid metallic iron. Their methodology was essentially the same as Eriksen et al [6] but the results showed a lower scatter and seemed to verify the method for such investigations. Their methodology was essentially the same as Eriksen et al [6] but the results showed a lower scatter and seemed to verify the method for such investigations.…”
Section: Introductionmentioning
confidence: 82%
“…Based on the data previously published by Seim and Kolbeinsen [7] and Eriksen et al [6], the ternary parameters are changed by a trial-and-error approach so that the iron saturation line in the system agrees with the experimental data. The work was performed using the FactSage™ thermodynamic software package, which utilizes the Modified Quasichemical Model to describe the liquid in the system in question.…”
Section: Thermodynamic Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The departure from chemical equilibrium is such that the partial pressure of oxygen for equilibrium between TiO 2 and Ti 2 O 3 in the slag is higher than for the Fe(metal)/FeO(slag) couple, which in turn gives a much higher oxygen activity than the C(metal)/CO(gas) couple. 3 While it has been argued that the calculated difference in the oxygen activity for the TiO 2 /Ti 2 O 3 and Fe/FeO couples is an artifact of the slag model used in the FactSage calculations, 4 there is little doubt that the difference with the C/CO couple is large, as confirmed by oxygen probe measurements. 5 Some calculated values are presented later in the paper; as an indication of the size of the effect, it can be noted that the typical carbon content of the iron product in ilmenite smelting is 2%, whereas the carbon content for equilibrium with the molten slag would be one order of magnitude smaller than this, around 0.2%.…”
Section: Introductionmentioning
confidence: 98%